INDUCTION OF ACETYLATION PROCESSES IN ANIMALS WITH SEROTONERGIC NEURON DYSFUNCTION REVERSES THEIR CAPABILITY OF LONG-TERM MEMORY FORMATION - O. V. Vorobiova; L. N. Grinkevich (Вавиловский журнал генетики и селекции, 2015)
The major tasks of neurobiology include the understanding of mechanisms governing long-term memory formation and search for means to improve memory. Animals with dysfunction of the serotonergic system are a convenient model for investigation of memory processes. The ablation of serotonergic neurons by the neurotoxin 5,7-DOT leads to inability of the mollusks to form an aversive food avoidance reflex. Previously we have found that epigenetic processes, such as histone methylation and acetylation, are involved in the formation of food aversion, and that disturbance of these processes leads to inability to form long-term memory. The goal of the current study was to investigate the possibility to reverse long-term memory in DOT-treated animals through the induction of acetylation processes. We found that treatment with histone deacetylase inhibitors NаB and Trichostatin А significantly increased the ability of DOT-treated animals to form the food aversion reflex. The results point to an important role of serotonin in the induction of the epigenetic processes mediating the formation of this type of long-term memory. By induction of acetylation processes, we managed to improve memory parameters significantly. Our “Neurodegeneration” model, based on ablation of serotonergic neurons, can be useful in studies of the epigenetic mechanisms underlying long-term memory destruction and screening of compounds crucial for memory formation.